A new genus and species of Parastenocarididae Chappuis, 1940 (Copepoda, Harpacticoida) from the Espinhaço Mountain Range (Brazil) with an unclear phylogenetic position within the Fontinalicaridinae Schminke, 2010 - Corgosinho, Paulo Henrique Costa; Rocha, Carlos Eduardo Falavigna Da; Neves, Gilmar Perbiche; Calixto, Bruno Rocha Athayde; Mendes, Maria Fernanda Lopes; Schizas, Nikolaos V. (Zootaxa, 2024)
Tupinicaris gen. nov. is proposed to accommodate a new hyporheic species of Parastenocarididae found in the northern portion of the Espinhaço mountain range (Minas Gerais, Brazil), in the Jequitinhonha River basin. Tupinicaris rupestris gen. et sp. nov. is included within the Fontinalicaridinae due to the presence of a long male and female pereopod five, the distal rim of which reaches beyond the middle of the next urosomite in the male or the middle of the genital double somite in the female; in the furca, the lateral setae are inserted on its proximal third, with a large gap occurring between them and the dorsal seta, which is inserted on the distal third; the female endopod of the pereopod 3 is a short blunt segment (although and unusually with a distal spine), and the female genital field is longer than its width. The new genus is supported by the presence of the following putative autapomorphies: Very long male and female outer spine on the first exopodite of pereopod 2, as long as 3/4 of the first and second exopodites combined; basis of male pereopod 3 with a small uncinate bulge proximally to the setiform endopod, first exopodite straight but expanding distally, followed by a scythe-shaped apophysis fused to the first exopodite, and hook-shaped thumb shorter than apophysis; basis of male pereopod 4 with a strong spinule inserted anteriorly to the thin and long endopod which is almost as long as the first exopodite; endopod of female pereopod 4 is longer than exopodite 1, almost reaching the tip of exopodite 2; pereopod 5 of male and female long, with 3 outer setae and a distal hyaline cushion probably representing a transformed seta; T-shaped female genital field more than two thirds longer than the whole length of the genital double somite; telson of male and female with a ventral and distally inserted medial and bifid spiniform processes, internal to the furcal insertion. The phylogenetic position of the new genus within the Fontinalicaridinae is unclear.